METODE IJTIHAD DALAM HUKUM ISLAM: Studi Pemikiran K.H. Ali Yafie dan H. M. Atho’ Mudzhar - Amrullah, Muh. Jazuli (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
The emergence of new ideas in the realm of thought and method of ijtihad that done by the jurists in through ijtihad is a necessity. In the midst of the problems of human life increasingly complex, the role of religious leaders in particular is very important in addressing any problems that occur. In this context appears K.H. Ali Yafie and HM Atho 'Mudzhar, which has its own characteristics and patterns of thought in the development of Islamic law. Conceptually K.H. Ali Yafie and   Atho 'Mudzhar offers ideas and methods that Islamic law could dialectic with social reality and social unrest. KH Ali Yafie maintain the classic methods of the previous scholars who contextualize the social reality as fard kifayah and fard 'ain, Nask mansukh. While H.M. Atho 'Mudzhar in thought and method of ijtihad, see a product of Islamic law not only of social reality, but also as a product of social history, as well as the influence of socio-political and socio-cultural. Implications of methods and ideas K.H. Ali Yafie is open mindset and thinking among Muslims, so that critical thinking and rational discourse to grow and thrive, while the implications of the method and thought HM Atho 'Mudzhar, for a mujtahid can not deny the history and influence of socio-cultural and socio-politics that surrounded it.